2014
DOI: 10.1186/ar4562
|View full text |Cite
|
Sign up to set email alerts
|

Scleroderma-polymyositis overlap syndrome versus idiopathic polymyositis and systemic sclerosis: a descriptive study on clinical features and myopathology

Abstract: IntroductionThe objective was to characterize the clinical and myopathologic features of patients with scleroderma-polymyositis (SSc-PM) overlap compared with a population of patients with systemic sclerosis (SSc) and polymyositis (PM).MethodsA three-way comparison of patients with SSc-PM overlap (n = 25) with patients with SSc (n = 397) and PM (n = 40) on clinical and myopathologic features and causes of death. One neuropathologist blinded for the diagnosis evaluated all recent available muscle biopsies. Biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 27 publications
(35 reference statements)
1
48
0
3
Order By: Relevance
“…Additional immunostaining in our study revealed increased MHC I expression in more than half of the biopsies. Although positive MHC I staining (up to 92%) has been reported by Bhansing and colleagues in scleroderma patients with polymyositis overlap (14), this is the first report of increased MHC I expression in a more diverse collection of weak scleroderma subjects.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Additional immunostaining in our study revealed increased MHC I expression in more than half of the biopsies. Although positive MHC I staining (up to 92%) has been reported by Bhansing and colleagues in scleroderma patients with polymyositis overlap (14), this is the first report of increased MHC I expression in a more diverse collection of weak scleroderma subjects.…”
Section: Discussionmentioning
confidence: 54%
“…In one large well-characterized scleroderma cohort, 1.3% (2/1,499) of SSc patients satisfied the 1975 Bohan and Peter diagnostic criteria for definite PM/DM (13). A range of muscle biopsy features have been described including inflammation and prominent necrosis (14,15). One study suggested that fibrosis was the prominent finding in muscle biopsies of weak scleroderma patients (16).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 47 OM patients (48%) developed ILD during follow‐up, which is significantly higher than in PM and DM patients (35% and 30.8%, respectively). Similarly, Bhansing et al described a significantly increased prevalence of pulmonary fibrosis in the overlap group compared to PM and primary SSc patients (83%, 53% and 49%, respectively). Other authors compared the clinical and serological features of myositis patients with and without overlap, and confirmed a higher frequency of extramuscular involvement in OM, supporting the hypothesis of a distinct entity …”
Section: Discussionmentioning
confidence: 79%
“…Patients with anti-PmScl antibodies have overlap syndromes between myositis and scleroderma. They are more likely to have myopathy and pulmonary disease [24]. Patients with scleroderma and anti-PmScl antibodies had fewer digital ulcers and cutaneous thickening or diffuse form while they had better pulmonary prognosis [25].…”
Section: Muscular Involvementmentioning
confidence: 99%